PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN WORDWALL UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI PADA MATERI BANGUN RUANG SISWA KELAS VII SMP ST.YOSEPH MEDAN - Ika Ruth Damayanti Hutabarat; Israil Sitepu; Imelda Sihombing; Friska Ledina Situngkir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by wordwall on improving students' numeracy literacy skills. Data were obtained through experiments with a pretest-posttest control group design in the experimental class (PBL assisted by wordwall) and the control class (conventional). The post-test results showed significant differences between the two classes: the experimental class had an average of 79.14 (the highest score was 95, the lowest was 20), while the control class had an average of 56.86 (the highest score was 70, the lowest was 15). The independent sample t-test statistical test confirmed the difference with a calculated t value of t = 10.8412 (greater than t table = 2.0345, indicating statistical significance at α = 0.05. In addition, the N-gain score analysis strengthened this finding with an increase in the numeracy literacy skills of the experimental class (N-gain = 0.75, high category) which was superior to the control class (N-gain = 0.57, medium category). The results of the study prove that the PBL model assisted by wordwalls is effective in significantly improving students' numeracy literacy compared to conventional models. The implications of this finding encourage recommendations for the use of interactive platforms such as wordwalls in problem-based learning to optimize numeracy competencies in the digital era.